The Influence of Price and Product Quality on Decision Making of "On Mada" Coffe Shops Visitors - Junaidi Mustapa Harahap; Mhd. Amin; Syafaruddin Siagian; Muhammad Irwansyah Hasibuan; Rina Asriani Levianti (Journal of Business and Economics Research (JBE), 2022)
The fast growth of coffee shops in Indonesia is similar to the widespread growth of coffee shops in other parts of the world. According to research, this is affected by how much coffee people in Indonesia drink. One reason why is that the choices people make affect how popular cafes are. The consumer's decision is based on how the customer feels about what was delivered and how it compares to what was expected. Along with the price, the quality of a product is often a factor in whether or not to buy it. Product quality is how well a customer thinks a product or service works overall. The goal of this study is to find out how pricing and product quality affect Rantauprapat coffee shops that are "on Mada." Based on the results of the data analysis and testing, it can be said that price does affect how people spend their money at the cafe, but product quality does not. The results of the Coefficient of Determination (R2) test show that price and product quality have a 39.6% effect on what customers decide to buy.